Short‐term impact of breast cancer screening intervention on health‐related quality of life in China: A multicentre cross‐sectional survey. Issue 9 (18th July 2019) - Zhu, Juan; Wang, Le; Huang, Hui‐Yao; Bai, Fang‐Zhou; Li, Jing; Fang, Yi; Wang, Yong; Mao, A‐Yan; Liao, Xian‐Zhen; Liu, Guo‐Xiang; Bai, Ya‐Na; Ren, Jian‐Song; et al.
Abstract: Objective: The impact of participating in breast cancer screening programmes on health‐related quality of life (HRQoL)is poorly understood. Methods: Based on a national breast cancer screening programme in China, a multicentre cross‐sectional survey was conducted covering 12 provinces from September 2013 to December 2014. HRQoL of participants in the screening population and general population was evaluated by the three‐levelEuroQol‐five‐Dimensions (EQ‐5D‐3L) instrument, and utility scores were generated through the Chinese value set. Univariate and multivariate regression analyses were performed to explore determinants of utility scores and anxiety/depression problems. Results: For screening group and general population (n = 4756, mean age = 51.6 year old), the corresponding utility scores were 0.937 (95% CI, 0.933‐0.941) and 0.953 (0.949‐0.957) ( P < .001). Pain/discomfort and anxiety/depression were the most common reported in both groups (51.4% and 34.3%, P < .001). Utility scores at prescreening, in‐screening, and postscreening interview timings were 0.928 (0.921‐0.935), 0.958 (0.948‐0.969), and 0.938 (0.933‐0.943), respectively ( P < .001); the corresponding proportions of anxiety/depression reporting were 25.9%, 16.3%, and 21.1%, respectively ( P  = .004). Interview timing, geographical region, and insurance status were associated with HRQoL and anxiety/depression in women at high‐risk of breast cancer. Conclusions: Utility scores of screening participants were significantly lower than that of general population in China, but the difference may be clinically insignificant. Further cohort studies using HRQoL measurements are needed.